1987
DOI: 10.1111/j.1365-2133.1987.tb12010.x
|View full text |Cite
|
Sign up to set email alerts
|

Etretinate treatment of severe cutaneous dysplasia in renal transplant recipients

Abstract: It is well recognized that patients who have undergone renal transplantation are at an increased risk of developing cutaneous malignancy. The incidence of this problem rises as survival time increases, and multiple dysplastic lesions may develop, especially on sun‐exposed sites. Conventional treatment by excision, curettage, cryotherapy or topical cytotoxic agents is often unsatisfactory because of the number and extent of lesions present. In non‐immunosuppressed patients, treatment with etretinate has been sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 0 publications
2
35
0
Order By: Relevance
“…Eleven patients were treated for at least 4 years, and although the mean reduction was still 1.63 SCCs, this did not quite achieve statistical significance (P=.09; 95% CI, 0.32 to −3.59). For individuals who had received at least 5,6,7,8,9, and 16 years of continuous treatment (n = 6, 6, 4, 4, 2, and 1, respectively), the mean difference in SCCs continued to show an overall reduction, but this was no longer statistically significant (Table 2, Figure 1). Responses for selected individual patients are shown in Figure 2.…”
Section: Effect Of Retinoids On the Number Of Sccs Per Yearmentioning
confidence: 91%
See 2 more Smart Citations
“…Eleven patients were treated for at least 4 years, and although the mean reduction was still 1.63 SCCs, this did not quite achieve statistical significance (P=.09; 95% CI, 0.32 to −3.59). For individuals who had received at least 5,6,7,8,9, and 16 years of continuous treatment (n = 6, 6, 4, 4, 2, and 1, respectively), the mean difference in SCCs continued to show an overall reduction, but this was no longer statistically significant (Table 2, Figure 1). Responses for selected individual patients are shown in Figure 2.…”
Section: Effect Of Retinoids On the Number Of Sccs Per Yearmentioning
confidence: 91%
“…Previous studies have also shown such a relapse in tumor development, 6,15,18,19,22 such that continuous treatment appears to be required to maintain a chemopreventive effect. It therefore seems most appropriate to regard retinoid chemoprevention as a potentially lifelong treatment in OTRs, and this must be considered before the patient embarks on such treatment.…”
Section: "Rebound" Scc Development During Interruption Of Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…1), and synthetic retinoids are currently used in the treatment of cancer, including both pre-malignant and malignant tumours of the skin (2)(3)(4). This concept of a favourable effect of exogenous vitamin A is supported by findings in animal experiments that pharmacological doses of both synthetic retinoids (5,6) and natural retinyl palmitate (7) inhibit chemical carcinogenesis in the skin.…”
Section: Introductionmentioning
confidence: 54%
“…Conventional treatment may be difficult due to the wide area of dysplastic skin. Etretinate 1 mgkglday was shown to have a beneficial role in a small group of RTRs (n = 6) by Shuttleworth et al [9]. The objectives of this study were to examine the therapeutic effects of low dose etretinate (0.3 mgkgl day) on the rate of skin cancer development in RTRs who had a history of excision of two or more skin cancers, to assess patient acceptability of this therapy, and to monitor retinoid toxic effects at this dose.…”
Section: Introductionmentioning
confidence: 98%